Skip to main content
Solve for x
Tick mark Image
Graph

Similar Problems from Web Search

Share

-6-3x+3\left(x-2\right)\left(x+2\right)\left(-1\right)=3x+6-1
Variable x cannot be equal to any of the values -2,2 since division by zero is not defined. Multiply both sides of the equation by 3\left(x-2\right)\left(x+2\right), the least common multiple of 2-x,x-2,3x^{2}-12.
-6-3x-3\left(x-2\right)\left(x+2\right)=3x+6-1
Multiply 3 and -1 to get -3.
-6-3x+\left(-3x+6\right)\left(x+2\right)=3x+6-1
Use the distributive property to multiply -3 by x-2.
-6-3x-3x^{2}+12=3x+6-1
Use the distributive property to multiply -3x+6 by x+2 and combine like terms.
6-3x-3x^{2}=3x+6-1
Add -6 and 12 to get 6.
6-3x-3x^{2}=3x+5
Subtract 1 from 6 to get 5.
6-3x-3x^{2}-3x=5
Subtract 3x from both sides.
6-6x-3x^{2}=5
Combine -3x and -3x to get -6x.
6-6x-3x^{2}-5=0
Subtract 5 from both sides.
1-6x-3x^{2}=0
Subtract 5 from 6 to get 1.
-3x^{2}-6x+1=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-\left(-6\right)±\sqrt{\left(-6\right)^{2}-4\left(-3\right)}}{2\left(-3\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -3 for a, -6 for b, and 1 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-6\right)±\sqrt{36-4\left(-3\right)}}{2\left(-3\right)}
Square -6.
x=\frac{-\left(-6\right)±\sqrt{36+12}}{2\left(-3\right)}
Multiply -4 times -3.
x=\frac{-\left(-6\right)±\sqrt{48}}{2\left(-3\right)}
Add 36 to 12.
x=\frac{-\left(-6\right)±4\sqrt{3}}{2\left(-3\right)}
Take the square root of 48.
x=\frac{6±4\sqrt{3}}{2\left(-3\right)}
The opposite of -6 is 6.
x=\frac{6±4\sqrt{3}}{-6}
Multiply 2 times -3.
x=\frac{4\sqrt{3}+6}{-6}
Now solve the equation x=\frac{6±4\sqrt{3}}{-6} when ± is plus. Add 6 to 4\sqrt{3}.
x=-\frac{2\sqrt{3}}{3}-1
Divide 6+4\sqrt{3} by -6.
x=\frac{6-4\sqrt{3}}{-6}
Now solve the equation x=\frac{6±4\sqrt{3}}{-6} when ± is minus. Subtract 4\sqrt{3} from 6.
x=\frac{2\sqrt{3}}{3}-1
Divide 6-4\sqrt{3} by -6.
x=-\frac{2\sqrt{3}}{3}-1 x=\frac{2\sqrt{3}}{3}-1
The equation is now solved.
-6-3x+3\left(x-2\right)\left(x+2\right)\left(-1\right)=3x+6-1
Variable x cannot be equal to any of the values -2,2 since division by zero is not defined. Multiply both sides of the equation by 3\left(x-2\right)\left(x+2\right), the least common multiple of 2-x,x-2,3x^{2}-12.
-6-3x-3\left(x-2\right)\left(x+2\right)=3x+6-1
Multiply 3 and -1 to get -3.
-6-3x+\left(-3x+6\right)\left(x+2\right)=3x+6-1
Use the distributive property to multiply -3 by x-2.
-6-3x-3x^{2}+12=3x+6-1
Use the distributive property to multiply -3x+6 by x+2 and combine like terms.
6-3x-3x^{2}=3x+6-1
Add -6 and 12 to get 6.
6-3x-3x^{2}=3x+5
Subtract 1 from 6 to get 5.
6-3x-3x^{2}-3x=5
Subtract 3x from both sides.
6-6x-3x^{2}=5
Combine -3x and -3x to get -6x.
-6x-3x^{2}=5-6
Subtract 6 from both sides.
-6x-3x^{2}=-1
Subtract 6 from 5 to get -1.
-3x^{2}-6x=-1
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
\frac{-3x^{2}-6x}{-3}=-\frac{1}{-3}
Divide both sides by -3.
x^{2}+\left(-\frac{6}{-3}\right)x=-\frac{1}{-3}
Dividing by -3 undoes the multiplication by -3.
x^{2}+2x=-\frac{1}{-3}
Divide -6 by -3.
x^{2}+2x=\frac{1}{3}
Divide -1 by -3.
x^{2}+2x+1^{2}=\frac{1}{3}+1^{2}
Divide 2, the coefficient of the x term, by 2 to get 1. Then add the square of 1 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+2x+1=\frac{1}{3}+1
Square 1.
x^{2}+2x+1=\frac{4}{3}
Add \frac{1}{3} to 1.
\left(x+1\right)^{2}=\frac{4}{3}
Factor x^{2}+2x+1. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+1\right)^{2}}=\sqrt{\frac{4}{3}}
Take the square root of both sides of the equation.
x+1=\frac{2\sqrt{3}}{3} x+1=-\frac{2\sqrt{3}}{3}
Simplify.
x=\frac{2\sqrt{3}}{3}-1 x=-\frac{2\sqrt{3}}{3}-1
Subtract 1 from both sides of the equation.